The Role of Student Cooperatives in Improving Entrepreneurship Spirit (Study on Cooperative Students of Gorontalo University) - Tirta Mulyadi; Fadali Rahman; Idris Yanto Niode; Zulkifli Zulkifli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study was conducted to describe the abilities obtained by students when they became members of a student cooperative and the role of student cooperatives in increasing the entrepreneurial spirit for students. The research design used in this study is qualitative research with a case study approach. The location of the research was carried out at the student cooperative of the University of Gorontalo. The data collection techniques used in this study were direct observation, interviews and documentation. Meanwhile, the data analysis techniques used by researchers are data reduction, data presentation, and data verification. The results of the study show that: 1) the abilities obtained by members in student cooperatives include Leadership abilities (leadership), the ability to control themselves and the ability to communicate (public speaking), 2) the existence of student cooperatives is one indicator that the role of student cooperatives can increase the spirit of entrepreneurship among students. As previously explained, the existence of student cooperatives is not just a process of running the cooperative, but more importantly, there is a domino effect obtained by students, which is to awaken the spirit of entrepreneurship. In order to provide knowledge about entrepreneurship and running cooperatives, the University of Gorontalo student cooperatives design and run various programs as a support in forming the spirit and knowledge of entrepreneurship or the procedures for running cooperatives that are good and right in various ways, for example making seminars.